Somatostatin Analogue Treatment of a TSH-Secreting Adenoma Presenting With Accelerated Bone Metabolism and a Pericardial Effusion: A Case Report. Issue 2 (January 2016) - Mousiolis, Athanasios C.; Rapti, Eleni; Grammatiki, Maria; Yavropoulou, Maria; Efstathiou, Maria; Foroglou, Nikolaos; Daniilidis, Michalis; Kotsa, Kalliopi
Abstract : Abstract: Increased bone turnover and other less frequent comorbidities of hyperthyroidism, such as heart failure, have only rarely been reported in association with central hyperthyroidism due to a thyrotropin (TSH)-secreting pituitary adenoma (TSHoma). Treatment is highly empirical and relies on eliminating the tumor and the hyperthyroid state. We report here an unusual case of a 39-year-old man who was initially admitted for management of pleuritic chest pain and fever of unknown origin. Diagnostic work up confirmed pericarditis and pleural effusion both refractory to treatment. The patient had a previous history of persistently elevated levels of alkaline phosphatase (ALP), indicative of increased bone turnover. He had also initially been treated with thyroxine supplementation due to elevated TSH levels. During the diagnostic process a TSHoma was revealed. Thyroxine was discontinued, and resection of the pituitary tumor followed by treatment with a somatostatin analog led to complete recession of the effusions, normalization of ALP, and shrinkage of pituitary tumor. Accelerated bone metabolism and pericardial and pleural effusions attributed to a TSHoma may resolve after successful treatment of the tumor. The unexpected clinical course of this case highlights the need for careful long-term surveillance in patients with these rare pituitary adenomas.